Research of the locus of control as correlate of professional success of sportsman - Гемонова [Gemonova T.] Тетяна Олександрівна; Кукурудзяк [Kukurudzyak I.] Ігор Володимирович (Slobozhanskyi Herald of Science and Sport, 2012)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–> <!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–> This paper considers the phenomenon of the locus of control, its typology and features and it makes the theoretical and analytical review of relationship between professional realization of the person and his type of the locus of control. It defines a goal, which is a practical study of interrelation between the internal and external locus of control and professional sports achievements. For the purpose the empirical studies conducted. The result revealed that the internal locus of control is more favorable for professional self-actualization athlete, that is due to the peculiarities of the total internal organization internals. <!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–> <!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>